2021
DOI: 10.3389/fimmu.2021.682853
|View full text |Cite
|
Sign up to set email alerts
|

Metformin, Macrophage Dysfunction and Atherosclerosis

Abstract: Metformin is one of the most widely prescribed hypoglycemic drugs and has the potential to treat many diseases. More and more evidence shows that metformin can regulate the function of macrophages in atherosclerosis, including reducing the differentiation of monocytes and inhibiting the inflammation, oxidative stress, polarization, foam cell formation and apoptosis of macrophages. The mechanisms by which metformin regulates the function of macrophages include AMPK, AMPK independent targets, NF-κB, ABCG5/8, Sir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 212 publications
(320 reference statements)
1
59
2
3
Order By: Relevance
“…A strong correlation between matrix metalloproteinase 9 (MMP-9) and HMGB1 levels, which was associated with poor outcomes, has been reported in ischemic stroke patients [ 75 ]. Various studies have demonstrated that blocking or modulating HMGB1 by compounds such as statins or by RNA interference provide neuroprotective effects against ischemic stroke [ 76 , 77 ]. Recently, HMGB1 has been studied for its role in epilepsy.…”
Section: Resultsmentioning
confidence: 99%
“…A strong correlation between matrix metalloproteinase 9 (MMP-9) and HMGB1 levels, which was associated with poor outcomes, has been reported in ischemic stroke patients [ 75 ]. Various studies have demonstrated that blocking or modulating HMGB1 by compounds such as statins or by RNA interference provide neuroprotective effects against ischemic stroke [ 76 , 77 ]. Recently, HMGB1 has been studied for its role in epilepsy.…”
Section: Resultsmentioning
confidence: 99%
“…In renal tubular epithelial cells, metformin inhibited senescence and alleviated diabetic nephropathy through the muscleblind-like 1 /miR-130a-3p/STAT3 signaling pathway 175 . In addition, metformin repressed endothelial senescence by activating the activity of Sirt1 176 , and inhibited macrophage senescence and SASP by down-regulating NLRC4 phosphorylation 177 . Śmieszek A et al 178 found that metformin suppressed SASP and senescence in ex vivo cultures of murine olfactory ensheathing cell via down-regulation of NF-κB signaling.…”
Section: Molecular Mechanisms and Signal Transduction Pathwaysmentioning
confidence: 97%
“…Nuclear hyperacetylation is also accomplished via increased histone-acetylase (HAT) activity as well as decreased histone-deacetylase (HDAC) activity [ 7 , 8 , 9 ]. Several agents including metformin, resveratrol, and curcumin (which all enhance sirtuin 1 (SIRT1) deacetylase activity) decrease extracellular HMGB1 release and reduce HMGB1-dependent inflammation [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Decreased activity of SIRT1, a nicotinamide adenine dinucleotide-dependent HDAC, occurs in aging and senescence, suggesting a role for HMGB1 in the inflammation associated with aging (“inflammageing”) [ 19 , 20 , 21 ].…”
Section: Extracellular Hmgb1 Releasementioning
confidence: 99%